Papulonecrotic tuberculid: report of a clinical case - Ana Brinca; Pedro Andrade; Ricardo Vieira; Américo Figueiredo (PAGEPress Publications, 2011)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Papulonecrotic tuberculid is a rare, chronic, recurrent and symmetric eruption of necrotizing skin papules arising in crops, involving primarily the limbs. It occurs in less than 5% of active tuberculosis. Typically bacilli are not detected in any of the cutaneous lesions. Extracutaneous tuberculosis primary focus is only detected in 30-40% of the cases, being the lymph nodes the most common location. Anti-tuberculosis treatment is rapidly effective and is often the main confirmation of the diagnosis.